1999
DOI: 10.21608/taec.1999.12639
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Maloideae (Rosaceae) 1- Chaenomeles Lindley and Cydonia Miller

Abstract: Macromorphological characters, SEM of seed coat surface criteria, seed coat anatomy and seed protein electrophoresis aspects, were used to reassess the taxonomic relationships between the genera Chaenomeles and Cydonia. Characters were analyzed by the NTsys-pc. program package, using the UPGMA clustering method. The dendrograms produced were discused and showed a close relationship between Chaenomeles sinensis Koehne and Cydonia oblonga Miller. The result gives support to the merging of the former taxon in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
0
0
1
Order By: Relevance
“…що робить їх дуже посухостійкими і невимогливими до складу і родючості ґрунту (Loutfy et al,1999;Lingdi et al, 2003). Для Ch.…”
Section: результати та їх обговоренняunclassified
“…що робить їх дуже посухостійкими і невимогливими до складу і родючості ґрунту (Loutfy et al,1999;Lingdi et al, 2003). Для Ch.…”
Section: результати та їх обговоренняunclassified
“…[13,14]. Weber (1964) reported that Cydonia, Malus and Pyrus L. could hybridize among themselves; thus, the various positions of Chaenomeles in different datasets suggests that the evolutionary origin of this genus may be complex, and likely involved hybridization [15].…”
Section: Introductionmentioning
confidence: 99%